Influence of binder in iron matrix composites - S., Shamsuddin; Shamsul Baharin, Jamal, Prof. Dr.; Z., Hussain; Z. A., Ahmad (American Institute of Physics, 2010)
Link to publisher's homepage at http://proceedings.aip.org/